1978
DOI: 10.1017/s0043174500050372
|View full text |Cite
|
Sign up to set email alerts
|

Competition of Four Morningglory(Ipomoeaspp.) Species with Cotton(Gossypium hirsutum)

Abstract: Tall morningglory [Ipomoea purpurea(L.) Roth.], pitted morningglory(I. lacunosaL.), ivyleaf morningglory [I. hederacea(L.) Jacq.] and entireleaf morningglory(I. hederaceavar.integruisculaGray) were compared for their competitive ability with cotton(Gossypium hirsutumL.) at weed densities of 4, 8, 16 and 32 weeds/15 m of row. Tall morningglory was the most competitive with yield reductions of as much as 88% at 32 weeds/15 m. The higher populations of tall morningglory also significantly reduced cotton populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
2

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 6 publications
6
51
2
Order By: Relevance
“…Other researchers had reported similar results that yield reduction caused by weed competition was primarily a result of reduction in cotton boll number and weight (Castner et al 1989;Tingle and Steele 2003). Both boll weight and seed number per boll were reduced to some extent in some of the goosegrass competition treatments while the lint percentage was not affected by goosegrass competition, which was consistent with the earlier studies (Buchanan and Burns 1971a, b;Crowley and Buchanan 1978). The cotton seed index was also not affected by goosegrass competition, which was in agreement with Buchanan and Burns (1971b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other researchers had reported similar results that yield reduction caused by weed competition was primarily a result of reduction in cotton boll number and weight (Castner et al 1989;Tingle and Steele 2003). Both boll weight and seed number per boll were reduced to some extent in some of the goosegrass competition treatments while the lint percentage was not affected by goosegrass competition, which was consistent with the earlier studies (Buchanan and Burns 1971a, b;Crowley and Buchanan 1978). The cotton seed index was also not affected by goosegrass competition, which was in agreement with Buchanan and Burns (1971b).…”
Section: Discussionsupporting
confidence: 90%
“…Goosegrass at various densities did not significantly affect fiber length, fiber length uniformity, micronaire, breaking elongation and fiber strength of the hand-harvested samples. This result was similar to earlier reports that fiber quality traits were not as sensitive as cotton yield in assessing weed interference effects (Crowley and Buchanan 1978;Smith et al 2000;Barnett and Steckel 2013). However, other studies have indicated that certain weed species, including ivyleaf morningglory (I. hederacea), hogpotato (Hoffmanseggia glauca), unicorn-plant, and johnsongrass, could reduce fiber quality at high densities (Mercer et al 1987;Castner et al 1989;Rogers et al 1996;Wood et al 2002).…”
Section: Discussionsupporting
confidence: 90%
“…The results of our study indicated that Ivy-leaved morning-glory was more tolerant to water stress than other weed species of morning-glory. These results were similar to those reported by Crowley and Buchanan (1978).…”
Section: Effect Of Osmotic Stress On Germinationsupporting
confidence: 93%
“…The species is, thus, not eliminated because the seeds on the soil surface remain dormant. Ipomoea hederacea is a successful competitor in agricultural fields (Crowley & Buchanan 1978) but little is known about its ability to compete for water and nutrients in abandoned fields. Parrish & Bazzaz (1976) suggested that I. hederacea is an ineffective competitor for nutrients and the purpose of this study was to test the hypothesis that the species is eliminated, or becomes a minor species in the vegetation of abandoned fields, because it is a poor competitor for nitrogen.…”
Section: Introductionmentioning
confidence: 99%